FAKTOR PENENTU MINAT PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Vinsensius Okto; Fajar Rina Sejati; Sahrul Ponto (CV. Denasya Smart Publisher, 2025)
This research aims to examine the influence of convenience, business expectations, and social factors on interest in using accounting information systems. The population in this study were employees of Bank Syariah Indonesia in Jayapura. The questionnaire data that can be processed has been filled in by 87 respondents. The data analysis technique uses multiple regression analysis. The research results show that convenience, business expectations, and social factors have a significant positive effect on the interest of Bank Syariah Indonesia employees in Jayapura City in using accounting information systems.